1999
DOI: 10.1159/000007233
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Antibacterial Activity of Men 10700, a New Penem Antibiotic

Abstract: We report here the antibacterial activity of the new penem antibiotic Men 10700 against a total of 740 gram-positive and gram-negative clinical isolates, in comparison to imipenem, meropenem, cefotaxime, ceftriaxone, ciprofloxacin and gentamicin. Men 10700 has shown a wide spectrum of antibacterial activity, with a potent activity both against gram-positive species (with the exception of methicillin-resistant Staphylococcus aureus and Staphylococcus epidermidis) as indicated by minimal inhibitory concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 14 publications
(14 reference statements)
1
6
0
Order By: Relevance
“…MEN 10700 showed modest activity only on Acinetobacter spp. and S. marcescens with MIC 90 of 116 and 16 mg/l, respectively: the modest activity on S. marcescens, however, was only seen in the present study, as in previous ones [9][10][11] MIC 90 values were equal to 2-4 mg/l.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…MEN 10700 showed modest activity only on Acinetobacter spp. and S. marcescens with MIC 90 of 116 and 16 mg/l, respectively: the modest activity on S. marcescens, however, was only seen in the present study, as in previous ones [9][10][11] MIC 90 values were equal to 2-4 mg/l.…”
Section: Discussionsupporting
confidence: 58%
“…In previous studies, MEN 10700 showed a broad spectrum of activity [9][10][11], including gram-positive and gram-negative strains, with the only notable exception of P. aeruginosa. In addition, MEN 10700 exhibited a good level of activity against anaerobes [12], against both meningococci and gonococci [13] and against resistant strains, such as penicillin-resistant S. pneumoniae [14].…”
Section: Discussionmentioning
confidence: 90%
“…Following single intramuscular injection, imipenem exceeded the minimum inhibitory concentrations for most sensitive respiratory pathogens till 12 h. In this respect, Varotto et al [10] found that imipenem had a good potential for treating a wide range of bacterial infections. Imipenem was rapidly absorbed and the peak plasma concentration was 9.99 g ml -1 .…”
Section: Time Of Samplingmentioning
confidence: 99%
“…20 Although MEN 10700 had a similar MIC to that of meropenem against Enterococcus sp (MIC for 90% of tested strains [MIC 90 ] = 8 mg/L), higher MIC 90 values were recorded with imipenem (32 mg/L), cefotaxime (64 mg/L), and ceftriaxone (64 mg/L), and the lowest MIC 90 values were recorded with ciprofloxacin (2 mg/L). 13 Another study showed that MEN 10700 had similar MICs to those of meropenem and imipenem in most gram-positive and gram-negative clinical isolates tested, with the exceptions of Morganella morganii, Serratia marcescens, and Acinetobacter sp, where MICs were lower for the carbapenems. 21 The greatest bactericidal effects of MEN 10700 were seen 4-6 hours after incubation with bacterial cultures, at which time a 2-3 and 3-4 log decline in colony-forming units was observed at 2 and 4-8 times the MIC of MEN 10700, respectively.…”
Section: Men 10700mentioning
confidence: 96%
“…Penems have a higher affinity for many PBPs than do many other ␤-lactams. 3 This is particularly noted for PBP2b, which may partly explain the good activity of penems against Streptococcus pneumoniae isolates with reduced sensitivity to penicillin G. 3 Penems tend to have a broader spectrum than do penicillins and cephalosporins 13 ; this is due to their smaller size (typically around 300 daltons) and favorable ionization characteristics. 3,14 These factors allow them access to PBPs of both gram-positive and gram-negative bacteria.…”
Section: Mechanism Of Actionmentioning
confidence: 99%